US Water Infrastructure Investment Long Overdue. Issue 3 (6th April 2022) - Qureshi, Naeem
Abstract : The United States has underinvested in water infrastructure for decades. Outdated water and wastewater systems across the nation are struggling to keep up with their infrastructure needs while utilities are burdened with expanding regulatory requirements and intensifying climate change scenarios.